Mozambique and Southern Africa karsts identification by SIG. - (:unkn) unknown (My University, 2022)
The Great East African Rift and South Africa are the rare areas in which hominin fossils several million years old have been found. The finds, in the “Cradle of Humanity (UNESCO)”, are made inside cavities protected from erosion. The old fauna discovered in Mozambican caves during the 2019 mission of the Human Origins in Mozambic & Malawi (HOMME) project (FOURVEL, 2021, this volume) indicates that this territory; located between these two great african fossiliferous regions, could contain an archaeo‐paleontological potential. To this end, doctoral research, started in March 2019, is funded by the 80Prime grant of the “Mission pour les initiatives transversales et interdisciplinaires” of the CNRS. The aim is to carry out a karstological survey in Mozambique to identify caves to be explored during future fieldwork sessions. In this article, we present a preliminary cartographic work, conducted prior to the fieldwork, dedicated to the preparation of survey maps.
Keywords: African Research